2017
DOI: 10.1161/strokeaha.117.017370
|View full text |Cite
|
Sign up to set email alerts
|

Brain Transforming Growth Factor-β Resists Hypertension Via Regulating Microglial Activation

Abstract: Background and Purpose Hypertension is the major risk factor for stroke. Recent work unveiled that hypertension is associated with chronic neuroinflammation; microglia are the major players in neuroinflammation and the activated microglia elevate sympathetic nerve activity and blood pressure (BP). This study is to understand how brain homeostasis is kept from hypertensive disturbance and microglial activation at the onset of hypertension. Methods Hypertension was induced by subcutaneous delivery of angiotens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 41 publications
3
19
0
Order By: Relevance
“…These studies showed changes in microglial morphology (enlarged soma, process retraction) and increased production of pro-inflammatory cytokines (IL-1β, IL-6, and TNF-α) [16][17][18]. Our results confirm that pressive Ang II leads to cerebral gliosis and extends this finding to another brain region, namely the hippocampus.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…These studies showed changes in microglial morphology (enlarged soma, process retraction) and increased production of pro-inflammatory cytokines (IL-1β, IL-6, and TNF-α) [16][17][18]. Our results confirm that pressive Ang II leads to cerebral gliosis and extends this finding to another brain region, namely the hippocampus.…”
Section: Discussionsupporting
confidence: 85%
“…We decided to examine TNF-α in more detail rather than IL-6, based on previous evidence that hypothalamic microglia isolated from Ang II-treated mice exhibit a significant increase in TNF-α expression and a milder increase in IL-6 [17,18]. In line with the proposed hypothesis, ELISA analysis of hippocampal homogenates revealed a significant increase in TNF-α levels in mice infused with Ang II 1000 ng/kg/min compared to controls (p = 0.040, Fig.…”
Section: Effect Of Ang II On Tnf-α Production In the Hippocampusmentioning
confidence: 99%
See 1 more Smart Citation
“…Early in TE12 infection, IFN-␥ was lower in IL-10 Ϫ/Ϫ mice than in WT mice, but later IFN-␥ production was higher and Th1 cells became more abundant. The reason for this change in pattern is not known, but microglial cells and NK cells can produce IFN-␥ independently of T cells in acute infection (47), and in the absence of IL-10, innate factors such as transforming growth factor ␤ (TGF-␤) may suppress IFN-␥ production prior to arrival of adaptive components of the immune response (48)(49)(50)(51)(52). Because TGF-␤ can induce the differentiation of Th17 cells (53-58), a potential dose-and cytokine-dependent role for TGF-␤ in the differential responses of TE12-and NSV-infected IL-10-deficient mice is under investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Epithelial Na + channel (ENaC), which could be active by furin, associates with increased blood pressure [14]. However, transforming growth factor (TGF-β) is also activated by furin but it contributes to lower blood pressure [27]. BNP activated by furin associates with low blood pressure through its diuretic and vasodilatory actions.…”
Section: Association Between Plasma Furin Levels and Clinical Parametersmentioning
confidence: 99%